Pengaruh Budaya Organisasi Terhadap Kinerja Guru di Madrasah Aaliyah Negeri 1 Bandar Lampung: Penelitian - Surotjudin, Ahmad; Subandi, Subandi; Wachidah, Nor Rochmatul; Habibie, M Luqmanul Hakim (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
Organizational culture is understood as a set of attitudes and behaviors that foster comfort and facilitate positive relationships and interactions. A positive organizational culture is believed to enhance work motivation and job satisfaction, whereas a negative culture may lead to decreased motivation. This study aims to assess the extent to which organizational culture is implemented and to examine its influence on teacher performance at MAN 1 Bandar Lampung. The research employed a quantitative method, with a population and sample size of 82 respondents. Data were collected using a Likert-scale questionnaire. Data analysis techniques included normality and linearity tests, while hypothesis testing was conducted using the t-test and simple linear regression. Based on the results of the Pearson correlation analysis using a one-tailed test, the correlation coefficient was r = 0.724 with a significance value of sig = 0.000 (sig < 0.01). This indicates a strong and significant relationship between organizational culture and teacher performance. The coefficient of determination (R²) was 0.525, suggesting that organizational culture contributes 52.5% to the performance of teachers at MAN 1 Bandar Lampung, while the remaining 47.5% is influenced by other factors. Therefore, the null hypothesis (H₀) is rejected and the alternative hypothesis (Hₐ) is accepted. This confirms that organizational culture has a positive influence on teacher performance at MAN 1 Bandar Lampung.